The Fluency of Oral Reading with Natural Reader Software - Varia Virdania Virdaus; Saiful Rifa’i (Journal of Development Research, 2021)
This recent investigation aims to find out whether natural reader software improves oral reading fluency for English language learners. In this recent study, the natural reader software was considered as independent variable and the oral reading fluency score was regarded as dependent one. The subjects of this investigation were students of English education study program. The number of the students of group (1) were 32 students who are taught using natural reader software and this group was considered to be an experimental group and The number of the students of group (2) were35 students who are taught without using natural reader software this group was considered to be control group. This study has proven that this software can significantly prove that most of students have more accurate and more precise reading skills. This study has revealed that oral reading fluency instruction does improve global reading proficiency at all grade levels